THE CONCEPTUAL APPARATUS IN FINANCE - N. M. Sabitova (Финансы: теория и практика, 2017)
In the Russian financial literature there is no unanimity of views on the conceptual apparatus. The notion of finance arose in the Russian financial science in the early XX century and was strongly influenced by the ideas of Marxism. Today most of the coursebooks continue to focus on this approach. Though in recent years in the scientific literature there is a movement attesting to the desire of the scientific community to change the established views. This is due to the fact that part of the conceptual apparatus is inconsistent with its generally accepted counterparts in the global financial theory. The paper proves the need to clarify the conceptual apparatus in finance theory in terms of its unification with the definitions given by foreign sources, in particular the definition of finance. The paper considers different views on the notion of finance and its functions including the author’s opinion.The author believes that the financial science in Russia must evolve to meet the financial globalization trends and factors which have an impact on science.